DEVELOPING TEACHING MEDIA OF INTERACTIVE VIDEO CD TUTORIAL USING CAMTASIA STUDIO APLICATION AND MACROMEDIA FLASH - Wirasasmita, Rasyid Hardi; Putra, Yupi Kuspandi (Educatio, 2015)
This study is a R & D (research and development) that is the development research that aims to produce instructional media interactive tutorials CD video using Camtasia studio and macromedia flash to a language visual programming subject of educational informatics department of STKIP Hamzanwadi Selong as well as to find out the quality of The CD interactive media based on the media experts assessment, maerial expert and instructional expert. This cd Learning talk about the introduction of the Delphi programming language, the basic program, an example of making a simple program and database connections with Delphi. The results of a feasibility assessment of video tutorials learning media for visual programming language subjects are: (1) the percentage score of material expert assessment was 81.25%; (2) the percentage score of media expert assessment was 84.5%; (3) the percentage score of student response was 84.83%. Based on the results of the assessment and responses obtained, we can conclude that this instructional media of video tutorials on programming language of visual delphi is feasible to be used and developed. Keywords: learning media, video tutorials, Camtasia Studio, Macromedia Flash, programming language Delphi visual